1966
DOI: 10.1088/0031-9155/11/3/302
|View full text |Cite
|
Sign up to set email alerts
|

The use of the Miniature Silicon Diode as a Radiation Dosemeter

Abstract: The use of commercially available miniature silicon diodes as dosemeters, with particular reference t o their application to biomedical facilities a t cyclotrons, is discussed. They are simple and convenient, and their small size makes them ideal for use as beam profile detectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1968
1968
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…For clinical proton beams, the need for accurate dose distribution data, such as depth dose distributions and lateral dose profiles, is as great as for other radiation qualities used in radiation therapy. Also in this case, the silicon diode detector is of interest (Raju 1966, Koehler 1967, Verhey et al 1979, Rikner et al 1983, Vatnitsky et al 1999. However, in previous work an inconsistency in the response in the Bragg peak between n-type Si diode detectors and ionization chambers has been observed but not satisfactorily explained (Verhey et al 1979).…”
Section: Introductionmentioning
confidence: 93%
“…For clinical proton beams, the need for accurate dose distribution data, such as depth dose distributions and lateral dose profiles, is as great as for other radiation qualities used in radiation therapy. Also in this case, the silicon diode detector is of interest (Raju 1966, Koehler 1967, Verhey et al 1979, Rikner et al 1983, Vatnitsky et al 1999. However, in previous work an inconsistency in the response in the Bragg peak between n-type Si diode detectors and ionization chambers has been observed but not satisfactorily explained (Verhey et al 1979).…”
Section: Introductionmentioning
confidence: 93%
“…While several studies characterizing diode detectors used for proton dose measurements have been published over the last four decades, these studies have often shown mixed or less-than-desirable results when compared to ionization chamber detectors. (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) However, Grusell and Medin (11) showed that a highly doped p-type Si detector designed for use with protons had a response consistent with ionization chambers, which are considered the gold standard for dose measurements. In the present study, we present results from an evaluation of the commercially available PTW PR60020 p-type diode detector specifically indicated by the manufacturer for proton dose measurements.…”
mentioning
confidence: 99%